Predominance of Self-concept in Students with Antisocial Behavior of Callao - Palacios-Garay, Jessica (2019)
The objective of the research was to determine the predominant dimension that has more influence over the self-concept in students with antisocial behaviors. This work is of a substantive type, of a non- experimental cross-sectional design. The method used was the hypothetical deductive. The sample consisted of 98 adolescents with antisocial behavior, the sampling used was intentional non- probabilistic. The instrument used was AF-5 by Garcia and Musitu (1999). The results indicated that the self-concept that influences adolescents was emotional self-concept.